Chronic pain epidemiology : from aetiology to public health - Croft, Peter; Blyth, Fiona; Windt, Danielle van der (Oxford : Oxford University Press, 2010)
'Chronic pain is a major cause of distress, disability, and work loss, and it is becoming increasingly prevalent through the general move towards an ageing population, which impacts dramatically upon society and health care systems worldwide. Due to improvements in health care, it is becoming more common for patients to continue living with long-term illness or disease (rather than these being terminal). Yet little attention has been paid to chronic pain as a public health problem or to the potential for its prevention, even though it can be studied and assessed using concepts and ideas from classical epidemiology. This book takes an unusual approach in making a symptom the focus of public health research and policy. Written by leaders in the field of pain, it fills a gap in current literature by presenting chronic pain in terms of cause, impact, consequence and prevention. It presents individual conditions as examples of chronic pain, together with chapters that provide overviews on the assessment of pain and methodological issues behind population assessment. Chronic Pain Epidemiology - From Aetiology to Public Health provides an invaluable framework and basis for thinking about chronic pain and the potential for its prevention in public health terms. It will appeal to readers from public health, epidemiology and policy perspectives, and those involved in the treatment of pain - such as pain researchers, clinicians and specialists. It will also be an invaluable resource for postgraduate students studying pain management, public health, and epidemiology'--Provided by publisher
Part 4: Common pain syndromes 11. Introduction to part 412. The symptom of pain in populations, Danielle van der Windt13. Headache, Helen Boardman14. Pain in children, Gareth T Jones and Adriana Paola Botello15. Lifecourse influences on chronic pain in adults, Gary J Macfarlane16. Pain in older people, Elaine ThomasPart 5: Pain and disease 17. Introduction to part 5, Peter Croft18. Neuropathic pain, Blair H. Smith and Nicola Torrance19. Post-surgical pain, Julie Bruce20. Chronic chest pain, myocardial ischaemia and coronary artery disease phenotypes, Harry Hemingway, Justin Zaman and Gene Feder21. Cancer, Fiona Blyth and Frances BoylePart 6: Public health and chronic pain 22. Introduction to part 6, Fiona Blyth, Danielle van der Windt, Peter Croft23. Pharmacological treatments: the example of osteoarthritis, Weiya Zhang and Michael Doherty24. The potential for prevention: occupation, Gwenllian Wynne-Jones25. The potential for prevention: can we change a population's perspective on pain?, Rachelle Buchbinder26. The potential for prevention: overview, Peter Croft, Danielle van der Windt, Helen Boardman, Fiona Blyth.
Keywords: Pain -- epidemiology; Chronic Disease -- epidemiology; Chronic Disease -- prevention & control; Pain -- prevention & control